VISUALISASI 3D KOS MOSEIM SEBAGAI MEDIA PEMBELAJARAN MENGGUNAKAN TEKNIK AEC EXTENDED 3DS MAX - Belalawe, Benyamin Jago (STIKOM Uyelindo Kupang, 2019)
Making learning media can create an effective, interesting, interactive and fun learning process. The usefulness of using diverse learning tools will be able to create learning variations. Current technological developments, especially in fields such as 3D. Learning media, especially 3D-based learning, can help users learn 3D. AEC (Architectural, Engineer, Construction) Extended is an extension of 3D features to make it easier for users to create 3D designs. The results of this study will be able to help facilitate users in creating 3D objects.